Do Audit Quality and Corporate Governance Deter Earnings Management? A Moderated Model with Leverage in Indonesia’s Infrastructure Sector - Farid, Ahmad; Mulya, Ali Sandy (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2025)
This research intends to explore how the quality of external audits and effective corporate governance influence earnings management, with leverage acting as a moderating factor. The investigation focused on companies in the infrastructure sector that are listed on the Indonesia Stock Exchange from 2020 to 2023. The analytical method utilized in this study is SmartPLS 4 to evaluate the suggested hypotheses. The sample population for this research includes infrastructure companies listed on the Indonesia Stock Exchange within the timeframe of 2020 to 2023. The non-probability sampling technique, specifically purposive sampling, resulted in a final sample of 58 firms. Findings from the study reveal that the quality of external audits and effective corporate governance do not impact earnings management, either directly or when leverage is considered as a moderate factor. Moreover, the results indicate that leverage does not diminish the influence of external audit quality and corporate governance on earnings management.